Laboratory analysis of track gauge restraining capacity of center-cracked railway concrete sleepers with various support conditions. (December 2018) - César Bastos, Josué; Edwards, J. Riley; Dersch, Marcus S.; Andrawes, Bassem O.
Abstract: As the number of concrete railway sleepers has steadily grown in North America, the importance of understanding the performance and failure of these components has also increased. Concrete sleepers typically perform better than timber sleepers to maintain track geometry and have a longer expected service life. Nevertheless, there have been derailments that were caused by excessive increase of track gauge due to deteriorated concrete sleepers and fastening systems. As ballast support conditions are closely related to sleeper performance, there is a need to fully understand the behavior of poorly supported sleepers. To quantify the influence of support conditions on sleeper deflection and gauge widening, laboratory experiments were performed. Using a static structural loading frame, new and center-cracked concrete sleepers were subjected to different support conditions, engineered using rubber pads. Simulated conditions included center bound sleepers, newly tamped track, and track under high impact loads. This paper presents a correlation between ballast support conditions and their effect on concrete sleeper health and track gauge. Using statistical tools to analyze the experimental results, it is shown that there is no significant difference between new sleepers and lightly center-cracked sleepers. Even extreme deterioration at the sleeper center has little influence on the gauge widening effect due to sleeper bending. Moreover, the gauge widening effect due to pure concrete sleeper bending seemed to be minimal, but not insignificant when compared to the amount of track gauge increase due to other track infrastructure conditions. Therefore, railway accidents where damaged concrete sleepers fail to restrain track gauge are more likely to be related to the rail seat, fastening system, or other production problems rather than center cracking. Highlights: Railroad track gauge increase due to concrete sleeper bending is quantified. Various support conditions representing real railroad track are considered. Light and severely center-cracked sleepers are analyzed. Bending of center-cracked concrete sleepers does not seem to be a safety issue for railroad operations.